2021
DOI: 10.1002/mnfr.202100147
|View full text |Cite
|
Sign up to set email alerts
|

Apostichopus japonicus Oligopeptide Induced Heterogeneity in the Gastrointestinal Tract Microbiota and Alleviated Hyperuricemia in a Microbiota‐Dependent Manner

Abstract: Scope: This study aims to investigate the protective effect of Apostichopus japonicus oligopeptide (AJOP) on hyperuricemia, demonstrate the modulation of the gastrointestinal tract (GIT) microbiota, and clarify the underlying microbiota-dependent mechanism. Methods and Results: Hyperuricemic mice treated with AJOP and subjected to corresponding fecal microbiota transplantation (FMT) are used to observe the beneficial effects of AJOP and microbiota. Gene transcriptions are measured using quantitative real-time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 30 publications
3
26
0
Order By: Relevance
“…Gut microbiota, as an important component of the intestine, plays an active role in UA excretion [ 9 , 47 ]. In accordance, previous studies indicated that the anti-hyperuricemic effects of some oligopeptides were mediated by the gut microbiota, such as tuna meat oligopeptides [ 40 ], Val-Val-Tyr-Pro peptide [ 48 ], and Apostichopus japonicus oligopeptide [ 49 ]. As reported, the diversity of intestinal flora in the hyperuricemia group is generally lower than that in the normal group [ 50 ].…”
Section: Discussionsupporting
confidence: 85%
“…Gut microbiota, as an important component of the intestine, plays an active role in UA excretion [ 9 , 47 ]. In accordance, previous studies indicated that the anti-hyperuricemic effects of some oligopeptides were mediated by the gut microbiota, such as tuna meat oligopeptides [ 40 ], Val-Val-Tyr-Pro peptide [ 48 ], and Apostichopus japonicus oligopeptide [ 49 ]. As reported, the diversity of intestinal flora in the hyperuricemia group is generally lower than that in the normal group [ 50 ].…”
Section: Discussionsupporting
confidence: 85%
“…Both peptides, as potential microbiota modulators, reduced gut microbiota richness and diversity, altering the composition at the phylum and genus levels ( Fan et al., 2022 ). Apostichopus japonicus oligopeptide (AJOP) can significantly alleviate HUA, regulate UA metabolism, inhibit the activation of NLRP3 inflammasome and NF-kB-related signaling pathways, and restore the m6A methylation levels ( Lu et al., 2021 ). Furthermore, fecal microbiota transplantation (FMT) effectively alleviated HUA in mice by selectively modulating the corresponding pathways associated with AJOP treatment ( Lu et al., 2021 ), suggesting that the underlying mechanism of AJOP’s protective effect is partially dependent on the microbiota.…”
Section: Gut Microbiota As a Potential Therapeutic Target In Hua And ...mentioning
confidence: 99%
“…Apostichopus japonicus oligopeptide (AJOP) can significantly alleviate HUA, regulate UA metabolism, inhibit the activation of NLRP3 inflammasome and NF-kB-related signaling pathways, and restore the m6A methylation levels ( Lu et al., 2021 ). Furthermore, fecal microbiota transplantation (FMT) effectively alleviated HUA in mice by selectively modulating the corresponding pathways associated with AJOP treatment ( Lu et al., 2021 ), suggesting that the underlying mechanism of AJOP’s protective effect is partially dependent on the microbiota. In a mouse model of diet-induced HUA, both EH-JAP and EH-LEU inhibited UA biosynthesis and promoted UA excretion ( Wan et al., 2020 ), thereby alleviating the hyperuricemic phenotype.…”
Section: Gut Microbiota As a Potential Therapeutic Target In Hua And ...mentioning
confidence: 99%
See 1 more Smart Citation
“…6 As previously reported, Apostichopus japonicus oligopeptide (AJOP), prepared with an edible protein, is a safer alternative that exerts anti-HUA effects by rebalancing uric acid metabolism and inhibiting the NLRP3 inflammasome and NF-κB signaling pathway activation. 3,7 The various components and their multiple targets not only contribute to the comprehensive anti-HUA effects of AJOP but also hinder the further development of AJOP due to the unclear understanding of key peptides with anti-HUA effects. The purify-and-identify method has been widely used to screen peptides with distinct functions and structures via iterative rounds, but this method is one-sided, labor intensive and time-consuming.…”
Section: Introductionmentioning
confidence: 99%